Mapping the Americas : The Transnational Politics of Contemporary Native Culture - Huhndorf, Shari M. (Shari Michelle), 1965- (Book collections on Project MUSE., 2009)
In Mapping the Americas, Shari M. Huhndorf tracks changing conceptions of Native culture as it increasingly transcends national boundaries and takes up vital concerns such as patriarchy, labor and environmental exploitation, the emergence of pan-Native urban communities, global imperialism, and the commodification of indigenous cultures.While nationalism remains a dominant anticolonial strategy in indigenous contexts, Huhndorf examines the ways in which transnational indigenous politics have reshaped Native culture (especially novels, films, photography, and performance) in the United States and Canada since the 1980s. Mapping the Americas thus broadens the political paradigms that have dominated recent critical work in Native studies as well as the geographies that provide its focus, particularly through its engagement with the Arctic.Among the manifestations of these new tendencies in Native culture that Huhndorf presents are Igloolik Isuma Productions, the Inuit company that has produced nearly forty films, including Atanarjuat, The Fast Runner; indigenous feminist playwrights; Leslie Marmon Silko's Almanac of the Dead; and the multimedia artist Shelley Niro. Huhndorf also addresses the neglect of Native America by champions of "postnationalist" American studies, which shifts attention away from ongoing colonial relationships between the United States and indigenous communities within its borders to U.S. imperial relations overseas.This is a dangerous oversight, Huhndorf argues, because this neglect risks repeating the disavowal of imperialism that the new American studies takes to task. Parallel transnational tendencies in American studies and Native American studies have thus worked at cross-purposes: as pan-tribal alliances draw attention to U.S. internal colonialism and its connections to global imperialism, American studies deflects attention from these ongoing processes of conquest. Mapping the Americas addresses this neglect by considering what happens to American studies when you put Native studies at the center.